Adiponectin Inhibits NLRP3 Inflammasome Activation in Nonalcoholic Steatohepatitis via AMPK-JNK/ErK1/2-NFκB/ROS Signaling Pathways - Dong, Zhixia; Zhuang, Qian; Ye, Xin; Ning, Min; Wu, Shan; Lu, Lungen; Wan, Xinjian (Frontiers in Medicine, 2020)
Adiponectin, an adipose-derived adipokine, possesses a hepatoprotective role in various liver disorders. It has been reported that hypoadiponectinemia can affect with the progression of non-alcoholic fatty liver diseases (NAFLD). Inflammasome activation has been recognized to play a major role during the progression of NAFLD. This research aimed to explore the effect of adiponectin on palmitate (PA)-mediated NLRP3 inflammasome activation and its potential molecular mechanisms. Male adiponectin-knockout (adiponectin-KO) mice and C57BL/6 (wild-type) mice were fed a high-fat-diet (HFD) for 12 weeks as an in vivo model of non-alcoholic steatohepatitis (NASH). Serum biochemical markers, liver histology and inflammasome-related gene and protein expression were determined. In addition, the hepatocytes isolated from wide type mice were exposed to PA in the absence or presence of adiponectin and/or AMPK inhibitor. The activation of NLRP3 inflammasome was assessed by mRNA and protein expression. Furthermore, ROS production and related signaling pathways were also evaluated. In the in vivo experiments, excessive hepatic steatosis with increased NLRP3 inflammasome and its complex expression were found in adiponectin-KO mice compared to wild-type mice. Moreover, the expression levels of NLRP3 inflammasome pathway molecules (NFκB and ROS) were upregulated, while the phosphorylation levels of AMPK, JNK and Erk1/2 were downregulated in adiponectin-KO mice compared with wild-type mice. In the in vitro study, PA increased lipid droplet deposition, NF-kB signaling and ROS production. Additionally, PA significantly promoted NLRP3 inflammasome activation and complex gene and protein expression in hepatocytes. Adiponectin could abolish PA-mediated inflammasome activation and decrease ROS production, which was reversed by AMPK inhibitor (compound C). Furthermore, the results showed that the inhibitory effect of adiponectin on PA-mediated inflammasome activation was regulated by AMPK-JNK/ErK1/2-NFκB/ROS signaling pathway. Conclusion: Adiponectin inhibited PA-mediated NLRP3 inflammasome activation in hepatocytes. Adiponectin analogs or AMPK agonists could serve as a potential novel agent for preventing or delaying the progression of NASH and NAFLD.